2002
DOI: 10.1242/dev.129.9.2079
|View full text |Cite
|
Sign up to set email alerts
|

Regulation ofAPETALA3floral homeotic gene expression by meristem identity genes

Abstract: The Arabidopsis APETALA3 (AP3) floral homeotic gene is required for specifying petal and stamen identities, and is expressed in a spatially limited domain of cells in the floral meristem that will give rise to these organs. Here we show that the floral meristem identity genes LEAFY (LFY) and APETALA1 (AP1) are required for the activation of AP3. The LFY transcription factor binds to a sequence, with dyad symmetry, that lies within a region of the AP3 promoter required for early expression of AP3. Mutation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…To decipher the molecular mechanism underlying the synergistic action of LFY and UFO, we used a Dual Luciferase Reporter Assay (DLRA) to analyze their ability to activate promoters when transiently expressed in Arabidopsis protoplasts. We found that pAP3, the best characterized LFY-UFO target (Hill et al, 1998; Lamb et al, 2002), is strongly activated when LFY (or LFY-VP16, a fusion of LFY with the VP16 activation domain; Parcy et al, 1998) is co-expressed with UFO (or UFO-VP16) but not by either effector alone (Figure 1A and 1E). We also tested the promoter of RABBIT EARS ( RBE ), a gene expressed in petal primordia in a UFO-dependent manner (Krizek et al, 2006).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…To decipher the molecular mechanism underlying the synergistic action of LFY and UFO, we used a Dual Luciferase Reporter Assay (DLRA) to analyze their ability to activate promoters when transiently expressed in Arabidopsis protoplasts. We found that pAP3, the best characterized LFY-UFO target (Hill et al, 1998; Lamb et al, 2002), is strongly activated when LFY (or LFY-VP16, a fusion of LFY with the VP16 activation domain; Parcy et al, 1998) is co-expressed with UFO (or UFO-VP16) but not by either effector alone (Figure 1A and 1E). We also tested the promoter of RABBIT EARS ( RBE ), a gene expressed in petal primordia in a UFO-dependent manner (Krizek et al, 2006).…”
Section: Resultsmentioning
confidence: 97%
“…Several regulatory regions driving AP3 expression in early floral meristem have been identified, including the Distal Early Element (DEE) and the Proximal Early Element (PEE; Figure 2A; Hill et al, 1998). The DEE contains a predicted canonical LFYBS (Lamb et al, 2002; Figure S2A). Replacing this site by the high-affinity LFYBS from pAP1 did not enhance activation (Figure S2B) and mutating it only slightly reduced pAP3 activation (Figure S2C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations